1995
DOI: 10.2527/1995.73113409x
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and metabolic profiles associated with puberty in beef heifers1

Abstract: Rapid growth large frame (RL, n = 61) or average growth medium frame (AM, n = 71) biotype heifers fed to achieve either moderate (MOD, .6 kg/d) or high ADG (HI, 1.0 kg/d) were used to determine whether puberty occurs at similar body composition or metabolic status. A heifer was considered pubertal after being detected in estrus and then forming a functional corpus luteum. Live animal estimates of body composition and blood samples for assessment of metabolic status were taken at 13 +/- .2 d after estrus for al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
3
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 52 publications
6
34
3
13
Order By: Relevance
“…However, heifers on treatment High probably accumulated more adipose tissue, as evidenced by the greater BCS, indicating that energy intake altered body composition of heifers at puberty. Previous studies with different breeds also demonstrated that greater energy intake during the prepubertal period results in greater fat deposition in the carcass (McShane et al, 1989;Hall et al, 1995). In contrast to our results, most studies report an increase in BW at puberty in heifers offered greater energy diets (Baker et al, 1989;Hopper et al, 1993;Hall et al, 1995).…”
Section: Discussioncontrasting
confidence: 56%
“…However, heifers on treatment High probably accumulated more adipose tissue, as evidenced by the greater BCS, indicating that energy intake altered body composition of heifers at puberty. Previous studies with different breeds also demonstrated that greater energy intake during the prepubertal period results in greater fat deposition in the carcass (McShane et al, 1989;Hall et al, 1995). In contrast to our results, most studies report an increase in BW at puberty in heifers offered greater energy diets (Baker et al, 1989;Hopper et al, 1993;Hall et al, 1995).…”
Section: Discussioncontrasting
confidence: 56%
“…We observed that animals were supplemented within a period of at least 120 days of each experimental protocol and reached BCS at a specific period of supplementation to achieve puberty earlier in life. Hall et al (1995) verified a BCS of 7.0 (scale from 1 to 9) at puberty in heifers with an increase rate of 1.0 kg day −1 . In the present study, we observed a correlation of -0.37 between the BCS and age of puberty indicating that the characteristics related to fat deposition influence puberty appearance.…”
Section: Discussionmentioning
confidence: 97%
“…The high correlation between longissimus muscle area and energy level after weaning is detected in Angus heifers (Hall et al, 1995). An important correlation between visual scores, live weights, and carcass traits obtained by ultrasound was found, which can be analyzed by univariate procedure (Pinto et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shiotsuki et al (2009) obtained a genetic correlation of 0.18 between HP at 18 months of age and carcass finishing score. In a study on puberty in beef heifers, Hall et al (1995) verified that rapid growth large frame heifers were younger at puberty and had greater body condition score. Therefore, body composition and growth rate are related to reproductive activity of the female (Martin et al, 1992;Hall et al, 1995).…”
Section: Genetic Correlationsmentioning
confidence: 99%